Perthes Disease in a Child With Osteogenesis Imperfecta From a Rare Genetic Variant: A Case Report - Hong, Pan; Zhao, Xiaolong; Liu, Ruikang; Rai, Saroj; Song, Yingying; Xu, Ruijing; Li, Jin (Frontiers in Genetics, 2022)
Background: Although certain genetic components have been reported as contributing factors for Perthes disease, its etiology remains unclear. We present a rare case of Perthes disease in a child with osteogenesis imperfecta (OI) caused by a mutation in the COL1A1 gene (NM_000088):exon25:c.1726C>T, (p.Gln576X). Case presentations: A 7-year-old boy was initially treated at our medical facility in March 2016 with a history of chronic pain in right hip joint and limping for a year. He was diagnosed as Perthes disease in the right hip joint. He underwent acetabular osteotomy and ipsilateral proximal femoral varus osteotomy for better containment. During the follow-ups, the right hip demonstrated a normal range of motion without pain, and the pelvic X-ray demonstrated Stulberg Type II hip joint with a round femoral head. In the latest admission in 2022, he suffered from a right femoral shaft fracture after petty violence. After reviewing his medical history, he was suspected of having OI. The whole exome sequencing demonstrated a gene mutation in COL1A1 (OMIM 166200) and confirmed the diagnosis of OI. Telescopic nailing was used to treat the femoral shaft fracture. After the nailing of the right femur, the appearance of the lower extremity seemed normal and symmetrical. Conclusion: This study revealed that there might be an association between OI and Perthes disease. Our case report enriches the phenotypes of osteogenesis imperfecta and provides insight into the pathogenesis of LCPD.